KONSEP KURIKULUM BERBASIS TAHFIDZ AL QURAN PPTQ MASJID AGUNG SURAKARTA - Annisa Regina Anandari; Luthfi Badrus Tsani; Nisa A-Zahro Jauzaa; Khuriyah (MAMBA'UL 'ULUM, 2023)
This study aims to determine the concept of curriculum based on Tahfidz Al-Qur'an Santri. The subject of this research is the PPTQ of the Great Mosque of Surakarta. This research is a qualitative research with data research methods through observation, interviews and documentation. Then data analysis uses data reduction, data presentation and data verification. The results found in this study indicate that the curriculum concept applied in the PPTQ of the Great Mosque of Surakarta is always repeating old memorization and adding new memorization regularly, scheduled and deposited with Asatidz (Teacher), repeating old memorization with close friends, evaluating carried out in the PPTQ of the Great Mosque of Surakarta carried out in several ways; 1) Sima'an, 2) Final Examination (Khataman Sugro and Khataman Kubro).